Effects of rivaroxaban on coagulation tests in patients with non-valvular atrial fibrillation under real-life conditions. Issue 154 (June 2017) - Silva, V.M.; Scanavacca, M.; Darrieux, F.; Cavalheiro-Filho, C.; Strunz, C.C.
Highlights: Sensitive PT tests may be useful in evaluating rivaroxaban concentration. Rivaroxaban plasma concentration presented low inter-individual variation. Laboratory assessment for rivaroxaban should not be ruled out.